The characteristics of the vertical distribution of radionuclide in free troposphere from simplified release scenarios: a case study - Sun, Xiangming; Chung, Keng Yeow; Dai, Qiudan (Nuclear Science and Technology, 2026)
Dose estimation in the upper air is not studied as much as on ground level or in boundary layer. However, there is a need from stakeholders in aviation industry for a reasonable estimation of the radioactive plume impact at cruising levels. This study aims to provide a quantitative estimation of the dose and how reliable it is for dispersion processes up to seven days. A Lagrangian atmospheric dispersion model is used to estimate quantitively the vertical extension of radionuclides from simplified hypothetical radionuclide release scenarios. Sources at different latitudes are selected for simulation in a boreal winter case. Three meteorological data are examined to test the sensitivity of vertical plume distribution to driving meteorological data. The vertical distribution of air concentration of radionuclides is investigated and the associated uncertainties are analysed. It is found that the vertical extension of plumes is sensitive to meteorological data being used where vertical turbulent velocities play an important role. It is therefore necessary to address the uncertainties of air concentration or dose in the free troposphere and caution must be taken when providing the results to stakeholders.